2014
DOI: 10.1371/journal.pone.0097914
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Interacts with pIgR Expressed by the Brain Microvascular Endothelium but Does Not Co-Localize with PAF Receptor

Abstract: Streptococcus pneumoniae is thought to adhere to the blood-brain barrier (BBB) endothelium prior to causing meningitis. The platelet activating factor receptor (PAFR) has been implicated in this adhesion but there is a paucity of data demonstrating direct binding of the bacteria to PAFR. Additionally, studies that inhibit PAFR strongly suggest that alternative receptors for pneumococci are present on the endothelium. Therefore, we studied the roles of PAFR and pIgR, an established epithelial pneumococcal recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
1
26
1
Order By: Relevance
“…Blocking of PAFR leads to a significant reduction of pneumococcal adhesion to endothelial cells in vitro, and complete absence of PAFR leads to less invasive pneumococcal disease in mouse models (4,7). However, we recently obtained data suggesting that a physical interaction between S. pneumoniae and PAFR is not likely to occur, as we did not observe colocalization between the receptor and the bacteria in the brain tissue of intravenously infected mice (10). Orihuela et al showed that the laminin receptor can initiate the contact of S. pneumoniae with the brain vascular endothelium in vivo (11).…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…Blocking of PAFR leads to a significant reduction of pneumococcal adhesion to endothelial cells in vitro, and complete absence of PAFR leads to less invasive pneumococcal disease in mouse models (4,7). However, we recently obtained data suggesting that a physical interaction between S. pneumoniae and PAFR is not likely to occur, as we did not observe colocalization between the receptor and the bacteria in the brain tissue of intravenously infected mice (10). Orihuela et al showed that the laminin receptor can initiate the contact of S. pneumoniae with the brain vascular endothelium in vivo (11).…”
contrasting
confidence: 55%
“…Orihuela et al showed that the laminin receptor can initiate the contact of S. pneumoniae with the brain vascular endothelium in vivo (11). The polyimmunoglobulin receptor (pIgR) can mediate binding of pneumococci to the epithelium of the upper respiratory tract (5,12), and we recently showed new evidence that pIgR is also implicated in binding of S. pneumoniae to brain endothelial cells (10). At the moment the extent of their contribution is unclear, and it remains to be established whether more receptors are involved in pneumococcal adherence to the blood-brain endothelium.…”
mentioning
confidence: 76%
“…Next, we used a bacteremia-derived meningitis mouse model (6,7,15) to study the role played by pilus-1 in meningitis development. Bacterial counts from brain homogenates demonstrated that mice infected with piliated invasive BHN191 had approximately 80% more pneumococci in the brain than did mice infected with the nonpiliated carriage isolate BHN460 ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Meningitis is usually caused by bacteria crossing from the bloodstream into the brain through the blood-brain barrier (BBB) (4). Pneumococcal translocation through the BBB is facilitated by receptor-mediated binding to the plasma membrane of endothelial cells (5)(6)(7). Previous reports have shown that the surface-anchored neuraminidase A (NanA) protein promotes pneumococcal invasion of brain endothelial cells (8) and that pneumolysin and choline-binding protein A (CbpA) are important for the development of invasive pneumococcal disease, including meningitis (9).…”
Section: Introductionmentioning
confidence: 99%
“…Pneumococci utilize a similar set of host surface receptors, including PAFR, for both adherence to the respiratory epithelium and for penetrating the endothelial lining of the blood-brain barrier [34]. In addition, poly immunoglobulin receptor (pIgR), which transports immunoglobulins across mucosal epithelium, and platelet endothelial cell adhesion molecule-1 (PECAM-1), involved in leukocyte migration and angiogenesis in the endothelium, have also been found to be utilized by pneumococci for endothelium adhesion and invasion [62,63]. It has been proposed that pneumococcal infection in itself may upregulate pIgR and PECAM-1 expression via a PAFR-mediated signalling mechanism [64].…”
Section: Central Nervous Systemmentioning
confidence: 99%